Lysozyme depolymerization of photo-activated chitosan adhesive films. (5th May 2015) - Mawad, Damia; Warren, Charles; Barton, Mathew; Mahns, David; Morley, John; Pham, Binh T.T.; Pham, Nguyen T.H.; Kueh, Sindy; Lauto, Antonio
Highlights: Lysozyme was loaded in chitosan boiadhesive to enhance rate of depolymerization. The impact of the laser used for adhesive photoactivation on lysozyme was assessed. Loading lysozyme in the bioadhesive enhanced the depolymerization rate. Irradiation with laser did not affect the depolymerization of adhesive by lysozyme. Abstract: Effective tissue bioadhesion of rose bengal–chitosan films can be achieved by photoactivation using a green laser. In this study, lysozyme was incorporated in these films to enhance the rate of depolymerization and assess the laser impact on lysozyme. The lysozyme loaded films exhibited a 21% mass loss after 4 weeks implantation in rats while control films (without lysozyme) had only 7% mass loss. Capillary electrophoresis–mass spectroscopy showed that chitosan degraded into monomers and oligomers of glucosamine and N -acetyl-glucosamine. Irradiation with laser did not affect the depolymerization of adhesive by lysozyme suggesting that the inclusion of lysozyme in the bioadhesive is a viable technique for tailoring the depolymerization.